Efficacy of oral glucocorticoid and cyclosporine in a case of rituximab-refractory type B insulin resistance syndrome - Takei, Masahiro (J Diabetes Investig, 2015)
We describe a case of type B insulin resistance syndrome associated with systemic lupus erythematosus (SLE) that was refractory to rituximab and successfully treated with a combination of oral glucocorticoids and cyclosporine. Prior to treatment, insulin resistance was severe, and application of a hyperinsulinemic euglycemic clamp was not possible despite the continuous intravenous infusion of insulin at a maximum rate of 9.0 mU/kg/min. The addition of cyclosporine to oral glucocorticoid therapy resulted in remission of insulin resistance. The combination of oral prednisolone and cyclosporine might be effective in treating type B insulin resistance syndrome, particularly in rituximab-resistant cases. However, nephrotoxicity is a particular concern for patients receiving long-term cyclosporine therapy.